Complex refractive index of volcanic ash aerosol in the infrared, visible, and ultraviolet - Deguine, Alexandre; Petitprez, Denis; Clarisse, Lieven; Gudmundsson, Snævarr; Outes, Ana Valeria; Villarosa, Gustavo; Herbin, Hervé (Applied Optics)
Very fine silicate-rich volcanic ash, generated by explosive volcanic eruptions, can efficiently be traced downwind with infrared satellite sounders. Their measurements can also be used to derive physical parameters, such as optical depths and effective radii. However, one of the key requirements for accurate retrievals is a good knowledge of the complex refractive index (CRI) of the ash under investigation. In the past, the vast majority of the studies used the CRIs from Pollack et al. [Icarus 19, 372 (1973)], which are based on measurements of thin slices of volcanic rock, and therefore are not representative for airborne volcanic ash particles. Here, we report measurements of the CRI of volcanic ash in suspension, generated from samples collected from recent high-impact eruptions in Chile (Puyehue-Cordón Caulle, Calbuco, and Chaitén), Iceland (Eyjafjallajökull and Grímsvötn), and Italy (Etna). The samples cover a wide range of SiO2 content (46% to 76%) as confirmed by an X-ray fluorescence analysis. In the experimental setup, volcanic ash was suspended in nitrogen through mechanical agitation. Extinction spectra were recorded in the infrared, visible, and ultraviolet spectral regions. The particle size distribution within the airflow was also recorded. An iterative algorithm allowed us to obtain fully consistent CRIs for the six samples, compatible with the observed extinction spectra and the Kramers–Krönig relations. While a good agreement is found with other recently reported CRIs in the UV/Vis, larger differences are found in the longwave infrared spectral region. Fil: Deguine, Alexandre. Universite Lille; Francia. Centre National de la Recherche Scientifique; Francia Fil: Petitprez, Denis. Universite Lille; Francia. Centre National de la Recherche Scientifique; Francia Fil: Clarisse, Lieven. Université Libre de Bruxelles; Bélgica Fil: Gudmundsson, Snævarr. Nature Research Center of Southeast Iceland; Islandia Fil: Outes, Ana Valeria. Consejo Nacional de Investigaciones Científicas y Técnicas. ...